Learners' Multimodal Displays of Willingness to Participate in Classroom Interaction in the L2 and CLIL Contexts. Issue 1 (2nd January 2017) - Evnitskaya, Natalia; Berger, Evelyne
Abstract: Drawing on recent conversation-analytic and socio-interactionist research on students' participation in L1 and L2 classroom interaction in teacher-fronted activities, this paper makes a step further by presenting an exploratory study of students' displays of willingness to participate (WTP) in classroom interaction and pedagogical activities across two educational and classroom settings (L2 classroom group work and CLIL classroom whole-class activity), both of which are characterized by the absence of teachers' next-speaker selection practices. The study focuses on occasions where students self-select to provide a sequentially relevant second pair-part within the current activity and how it is oriented to by co-participants, particularly when the expected action is not accomplished. Using a multimodal conversation analytic approach, it shows that students' WTP is indexed as a social, public demonstration of one's interest to engage in the ongoing activity through displays of attentiveness to unfolding interaction and learning activities, emerging turn-taking and speakership establishment, engaging in foci of attention and participation frameworks, and taking on relevant participant roles. These findings indicate that WTP is not an absolute and fixed concept but is rather constituted by different aspects or levels of engagement displayed by the participants in interaction on a moment-by-moment basis.